2017
DOI: 10.1002/etc.4014
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic biotransformation of N‐methyl perfluorobutanesulfonamido ethanol and N‐ethyl perfluorooctanesulfonamido ethanol

Abstract: Some fluorochemical products are manufactured using N-methyl perfluorobutanesulfonamido ethanol (MeFBSE), a short-chain replacement for perfluorooctyl-based chemistries N-methyl and N-ethyl perfluorooctanesulfonamido ethanols (EtFOSE). The present study shows for the first time the anaerobic biodegradation of MeFBSE and EtFOSE in municipal digester sludge under methanogenic conditions. Both MeFBSE and EtFOSE were incubated for 108 d with anaerobic digester sludge. Although sterile controls did not remove MeFBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated that anaerobic microbial activities play important roles in the transformation of some classes of PFASs, but not all of them. In cultures inoculated with anaerobic digester sludge, n :2 fluorotelomer alcohols (FtOHs) ( n = 6 or 8) were mainly transformed into n :2 and ( n –1):3 FtCAs and n :2 fluorotelomer unsaturated carboxylates (FtUCA) ( n = 6 or 8) . Similar biotransformations have also been observed in laboratory anaerobic bioreactors treating municipal solid waste containing disubstituted polyfluorinated phosphate esters (DiPAPs) .…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous studies have demonstrated that anaerobic microbial activities play important roles in the transformation of some classes of PFASs, but not all of them. In cultures inoculated with anaerobic digester sludge, n :2 fluorotelomer alcohols (FtOHs) ( n = 6 or 8) were mainly transformed into n :2 and ( n –1):3 FtCAs and n :2 fluorotelomer unsaturated carboxylates (FtUCA) ( n = 6 or 8) . Similar biotransformations have also been observed in laboratory anaerobic bioreactors treating municipal solid waste containing disubstituted polyfluorinated phosphate esters (DiPAPs) .…”
Section: Introductionmentioning
confidence: 60%
“…(18) Additionally, methanogenic cultures were demonstrated to convert N -methyl perfluorobutane sulfonamido ethanol (MeFBSE) and Nethyl perfluorooctane sulfonamido ethanol (EtFOSE) into their respective perfluoroalkyl sulfonamide acetates and perfluoroalkyl sulfinates. (19) In contrast, perfluoroalkyl sulfonamide acetates were recalcitrant to biotransformation in methanogenic culture, and FtSs were persistent in both methanogenic or sulfate-reducing cultures. (18,20) The lack of information about the anaerobic biotransformation of fluorotelomer thioethers highlights the importance of further studies of PFAS biotransformation at AFFF-impacted groundwater sites.…”
Section: Introductionmentioning
confidence: 99%
“…104,115 The anaerobic degradation of neutral ECF-based PFAS was found to be minimal by Yin et al, 114 while Lange found perfluoroalkyl sulfonamide acetic acids and perfluoroalkyl sulfonates as the transformation products, with half-life between 36 and 1860 days. 116 Accordingly, biotransformation of neutral PFAS would result in their reduced VI potential. Prior laboratory-based studies involving FTOHs and sludge, sediment, and soil indicated half-life anywhere from <1 to >365 days.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Representative microbial degradation technologies in recent years include marine sediments, aerobic soils, activated sludge, aquatic oligochaetes and mammals that can degrade and convert PFOS′s precursors . It is reported that 1 H, 1 H, 2 H, 2H‐perfluorooctane sulfonate (6:2 FTSA) can be degraded by a Pseudomonas strain D2, and 8:2 fluoroalcohol (8:2) FTOH) can be degraded by Pseudomonas strain OCY4 and OCW4, and PFOS can be used as the sole carbon source for their growth . Kwon et al.…”
Section: Figurementioning
confidence: 99%